Self‐Assembled Giant Vesicles Formed by Type I [3:3]‐Hexakis Adducts of C60 Equipped with Enantiomerically Pure cyclo‐Monomalonate Addends1. Issue 21 (23rd June 2015) - Ioannou, Charalambos P.; Ioannou, Georgios I.; Moushi, Eleni E.; Velonia, Kelly; Chronakis, Nikos
Abstract: An efficient route for the synthesis of two amphiphilic type I [3:3]‐hexakis adducts of C60 equipped with enantiopure cyclo ‐monomalonate addends was explored. Studies on their self‐assembling behavior by TEM and SEM revealed that minor modification of the size and chemical nature of their glycol‐substituted monomalonate addends and, consequently, of the shape of these giant molecules significantly influences their corresponding self‐assembling architectures. Abstract : Two giant, amphiphilic type I [3:3]‐hexakis adducts of C60 equipped with enantiomerically pure cyclo ‐monomalonate addends are prepared. Their self‐assembling behavior in water reveals that minor modification of the size and chemical nature of their monomalonate addends and, consequently, of the shape of these giant molecules significantly influences their self‐assembling architectures.